Implications and Impact of Digital Literacy on Higher Education: Systematic Literature Review - Ratih Komala Dewi; Oria Lasmana; Festiyed Festiyed; Asrizal Asrizal; Desnita Desnita; Skunda Diliarosta (Green Publisher Indonesia, 2024)
Digital literacy is the ability to interpret and use all information/data widely obtained with digital assistance. Digital literacy plays an important role in the industrial revolution 4.0 era because in this era there is an integration of advanced digital technology in all aspects of life including education. The purpose of this study is to investigate the application and impact of digital literacy in higher education. The method in this research is a systematic literature review with use PRISMA method. In this study, a process of identification, synthesis and analysis of scientific articles relevant to the impact of digital literacy on higher education was carried out. Digital literacy has a significant impact on higher education, shaping the way students and educators interact with information and technology. It is important for higher education institutions to integrate digital literacy in the curriculum, as well as address the challenges that arise, to ensure that students are prepared for future challenges in an increasingly digitized world.